Utilization Pattern of Mobile Apps Among Farmers for Agricultural Production (Indian Journal of Extension Education, 2022)
The study was undertaken in the four specifically chosen districts of Haryana state in diverse geographical locations and had different crop patterns. In a number of districts, the main cropping pattern was rice and wheat, combined with pearl millet and mustard. This study aimed to determine how agricultural mobile apps were used by farmers for agricultural productivity by using a utility index. In accordance with a well-planned and pre-tested interview schedule, the data were gathered from 240 respondents, including 15 respondents each from randomly chosen 16 villages. Utilization pattern checked for general information of agriculture practices, utilization of mobile apps for gaining market related information and utilization of mobile apps to contact the agriculture experts in order to find out the solution of agriculture problems. More than half of the respondents perceived medium level of utilization pattern of agriculture mobile apps on agricultural practices. To increase the extent to which farmers use agricultural mobile apps for agricultural production, outreach programs and trainings are required.